Pelaksanaan Etnoparenting Melayu Riau oleh Orang Tua untuk Menanamkan Nilai Kesopanan pada Anak Usia Dini di RA Plus Nur As-Syam Desa Kasikan Kecamatan Tapung Hulu Kabupaten Kampar - Alma Ida; Zulkifli N; Ria Novianti (Journal on Education, 2023)
This study aims to determine the implementation of Riau Malay ethnoparenting by parents to instill the value of decency in early childhood in Kasikan Village, Tapung Hulu District, Kampar Regency. The type of research used is descriptive qualitative research. The subjects of this study were 5 parents. Data was collected through observation, interviews and documentation. The results of the study show that parents apply 6 aspects of parenting based on a book of politeness and the spirit of Riau Malay, namely 1) straight intentions and beautiful nature 2) place oneself in a suitable relationship 3) be clever in carrying yourself 4) wisely consider wisely tolerating 5) willing to sacrifice willing to give in 6) be humble. Of these 6 aspects, 5 of them have been well implemented by parents to their children and 1 other aspect has been implemented quite well. Parents instill the values ​​of decency in early childhood by giving examples, advising and positive habituation. So for Riau Malay ethnoparenting parents this needs to be applied to instill the value of decency in children from an early age.